Plan de negocios-aplicación para la búsqueda de centros veterinarios especializados en Bogotá - Bulcao Machado, Rebecca; Moreno Gómez, Angie Melissa; Urrego Becerra, Wilder Stiven (Universidad Antonio Nariño, 2021)
This business proposal arises because at present there has been an increase in the use of applications to facilitate people's day-to-day lives. The rapid expansion of mobile telecommunications technology, both at the levels of networks and infrastructures, in services, applications and content, as well as at the level of development of sophisticated devices, are present directly and indirectly, in everyday life. of the citizen. (Ramírez, 2008). Likewise, it is identified that in households that have pets there is a need for competent and reliable professionals (veterinarians) to care for them.